Efficiency of dual test of SARS-CoV-2 antigen and nucleic acid among freight truck drivers and workers passing through expressway toll gates - Hang HONG; Ting FANG; Ke-qin DING (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo evaluate the efficiency of dual test of severe acute respiratory disease coronavirus 2 (SARS-CoV-2) antigen and nucleic acid among freight truck drivers and workers passing through expressway toll gates. MethodsDual tests of SARS-CoV-2 antigen and nucleic acid were conducted among 48 734 freight truck drivers and workers passing through 8 expressway toll gates in Ningbo city from provinces other than Zhejiang province during the period of March 20 - April 17, 2022. The test results were statistically analyzed. ResultsTotally 9 infections of SARS-CoV-2 Omicron variant were detected; of which, 6 were diagnosed clinically as mild coronavirus disease 2019 (COVID-19) case and 3 as asymptomatic infection. No subsequent COVID-19 case was confirmed. For the SARS-CoV-2 antigen test, the sensitivity and specificity were 55.5% (5/9) and 99.9% (48 717/48 725); the positive and negative predictive value were 38.5% (5/13) and 99.9% (48 717/48 721), respectively. For multiplex fluorescence PCR test of SARS-CoV-2 nucleic acid among the participants with positive SARS-CoV-2 antigen result, the Ct values of ORF1ab and N gene M (25th percentile, 75th percentile) were 19.0 (17.1, 21.5) and 19.0 (16.6, 22.5); while, the Ct values of the participants with negative result was significantly higher than those of the participants with positive SARS-CoV-2 antigen result (P < 0.05). ConclusionIn this study, the sensitivity of SARS-CoV-2 antigen test is low but the specificity of the test is high for the detection of SARS-CoV-2 infection. The results suggest that dual test of SARS-CoV-2 antigen and nucleic acid should be implemented to reduce the risk of imported case-induced local COVID-19 epidemic.